2018
DOI: 10.1186/s12967-018-1653-x
|View full text |Cite
|
Sign up to set email alerts
|

A lipidated bi-epitope vaccine comprising of MHC-I and MHC-II binder peptides elicits protective CD4 T cell and CD8 T cell immunity against Mycobacterium tuberculosis

Abstract: BackgroundThe clinical trials conducted at Chingleput India suggest that BCG fails to protect against tuberculosis (TB) in TB-endemic population. Recent studies advocate that non-tuberculous mycobacteria and latent Mycobacterium tuberculosis (Mtb) infection interferes in the antigen processing and presentation of BCG in inducing protective immunity against Mtb. Thereby, indicating that any vaccine that require extensive antigen processing may not be efficacious in TB-endemic zones. Recently, we have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Cumbersome therapeutic strategies, drug-resistant strains, and failures of the common BCG vaccine all further the necessity of efficacious vaccine development. Subunit vaccines have provided a benefit over whole cell-based vaccines [ 8 , 9 , 71 ]. Overall, our studies indicate that a multi T cell epitope-based DNA vaccine substantially enhances the immunity and protection of BCG against Mtb .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cumbersome therapeutic strategies, drug-resistant strains, and failures of the common BCG vaccine all further the necessity of efficacious vaccine development. Subunit vaccines have provided a benefit over whole cell-based vaccines [ 8 , 9 , 71 ]. Overall, our studies indicate that a multi T cell epitope-based DNA vaccine substantially enhances the immunity and protection of BCG against Mtb .…”
Section: Discussionmentioning
confidence: 99%
“…Spleen, lymph nodes (LNs), and lung cells were prepared by crushing of tissues followed by RBC lysis. Lymphocytes (2 × 10 5 /well) isolated from spleens/LNs or lungs were cultured in 96-well U bottom plates and stimulated with PPD (25 μg/ml) and 5 C6 peptides (5 μg/ml each) as Rv0476 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) was unable to synthesize. For DCs and macrophages activation status studies, cells were stimulated with LPS (1 μg/ml) for 24 h.…”
Section: Spleen and Lung Lymphocyte Culturementioning
confidence: 99%
See 1 more Smart Citation
“…L4.8 significantly elicited CD8 + and CD4 + T cells and was claimed for better protection against Mtb infection than BCG. It is, however, not approved clinically and needs validation on model organisms (Rai et al 2018). In 2019, an immunoinformatics based study from Elhag Mustafa et al reported four immunogenic peptides, from the conserved regions of the PPE65 family protein of Mycobacterium tuberculosis, along with the population coverage of these epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study highlighted that peptide nanofiber vaccines in combination with BCG reduce bacterial load in the lungs of Mtb -infected mice and thus may be an effective strategy for boosting BCG-primed individuals [ 79 ]. Moreover, some studies have suggested that developing subunit vaccines that include classical T-cell epitopes derived from proteins that are expressed by the active and latent form of the causative agent may represent a new frontier in tuberculosis vaccine research [ 80 , 81 ]. In this context, several supportive tools are used to predict the most suitable epitopes to involve in the vaccine design, including immunoinformatic, genomic, and proteomic approaches [ 39 , 82 , 83 , 84 ].…”
Section: Strategic Goals For New Tb Vaccine Developmentmentioning
confidence: 99%